Interpreting the Bible - Mickelsen, A. Berkeley (Grand Rapids, MI Eerdmans, 1963)
Contents : Source of the interpreter's principles - Lessons from the past - Crucial issues - The Bible as a unique book - Context - Language - History and culture - Short figures of speech - Opaque figues of speech - Extended figures of speech - Typology - Symbols and symbolical actions - Prophecy - Descriptive language of Creation and climax - Poetry - Doctrinal teachings - Devotion and conduct - Distortion thropugh artificial assumptions - Balance through care and practice. Includes bibliographical references and indexes.
Donated by Miss H. Cassidy on 21st February, 1980.
Keywords: Hermeneutics